Astroglial Connexins in Neurodegenerative Diseases - Huang, Xiaomin; Su, Yixun; Wang, Nan; Li, Hui; Li, Zhigang; Yin, Guowei; Chen, Hui; Niu, Jianqin; Yi, Chenju (Frontiers in Molecular Neuroscience, 2021)
Astrocytes play a crucial role in the maintenance of the normal functions of the Central Nervous System (CNS). During the pathogenesis of neurodegenerative diseases, astrocytes undergo morphological and functional remodeling, a process called reactive astrogliosis, in response to the insults to the CNS. One of the key aspects of the reactive astrocytes is the change in the expression and function of connexins. Connexins are channel proteins that highly expressed in astrocytes, forming gap junction channels and hemichannels, allowing diffusional trafficking of small molecules. Alterations of astrocytic connexin expression and function found in neurodegenerative diseases have been shown to affect the disease progression by changing neuronal function and survival. In this review, we will summarize the role of astroglial connexins in neurodegenerative diseases including Alzheimer’s disease, Huntington’s disease, Parkinson’s disease, and amyotrophic lateral sclerosis. Also, we will discuss why targeting connexins can be a plausible therapeutic strategy to manage these neurodegenerative diseases.